Resource based view of the firm as a theoretical lens on the organisational consequences of quality improvement - Burton, Christopher R. (Kerman University of Medical Sciences, 2014)
Evaluating the investment that healthcare organisations make in quality improvement requires knowledge of impact at multiple levels, including patient care, workforce and other organisational resources. The degree to which these resources help organisations to survive and thrive in the challenging contexts in which healthcare is designed and delivered is unknown. Investigating this question from the perspective of the Resource Based View (RBV) of the Firm may provide insights, although is not without challenge.